Changes in Energy Metabolism Trigger Pupal Diapause Transition of Bactrocera minax After 20-Hydroxyecdysone Application - Dong, Yong-Cheng; Chen, Zhen-Zhong; Clarke, Anthony R.; Niu, Chang-Ying (Frontiers in Physiology, 2019)
Correct timing of diapause entry and exit is critical for a species' survival. While many aspects of insect diapause are well-studied, the mechanisms underlying diapause termination remain largely unknown. The Chinese citrus fly, Bactrocera minax, is a univoltine insect with an obligatory pupal diapause. The application of 20-hydroxyecdysone (20E) is known to terminate diapause in B. minax, and we used this approach, along with isobaric tags for relative and absolute quantitation technology, to determine the proteins associated with diapause termination in this fly. Among 2,258 identified proteins, 1,169 proteins significantly differed at 1, 2, and 5 days post-injection of 20E, compared with the solvent-injected control group. Functional annotation revealed that the majority of differentially expressed proteins were enriched in the core energy metabolism of amino acids, proteins, lipids, and carbohydrates as well as in signal transduction pathways including PPAR signaling, Calcium signaling, Glucagon signaling, VEGF signaling, Ras signaling, cGMP-PKG signaling, and cAMP signaling. A combined transcriptomic and proteomic analysis suggested the involvement of energy metabolism in the response of diapause transition. RNA interference experiments disclosed that a 20E injection triggers diapause termination probably through non-genomic actions, rather than nuclear receptor mediated genomic actions. Our results provide extensive proteomic resources for insect diapause transition and offer a potential for pest control by incapacitating the regulation of diapause termination either by breaking diapause prematurely or by delaying diapause termination to render diapausing individuals at a high risk of mortality.